Investigation of Phase Change Mechanisms of n-Alkanes Injected in sub- and Supercritical Conditions - Rezaei, Javad; Rieß, Sebastian; Peter, Andreas; Weiß, Lukas; Wensing, Michael (ICLASS 2018, 14th Triennial International Conference on Liquid Atomization and Spray Systems, 2018)
In the mixing controlled Diesel combustion concept, mixing processes are a key phenomenon significantly effecting power, efficiency and emissions in Diesel engines. A consequence of fuel-air-mixing is the phase change of fuel, a process that in sprays is not fully understood yet. In this study, phase change mechanisms of sprays of different n-alkanes at high pressure and temperature conditions are investigated. Mie scattering imaging is utilized to obtain the maximum liquid penetration of Diesel surrogates (Hexane, Heptane, Decane and Dodecane) injected into Nitrogen atmosphere in a constant volume chamber at supercritical temperature (reduced temperatures of minimum 1,1) and ambient pressures ranging from sub- to supercritical regarding the fuel’s critical point. Two 1D models are utilized to predict the liquid length based on the required enthalpy for full phase change. Siebers scaling law is used based on the assumption of adiabatic saturation of ambient gas by the injected fuel. Thus, the phase change is considered to take place due to mass transfer dominated evaporation. A modified model used in this study is fundamentally based on Siebers model, but with the assumption of reaching the boiling or critical point due to pure heat transfer. The theoretical models are validated against experimental data to identify phase change regimes. Results show that mass transfer based evaporation is the dominant mechanism at low ambient pressures and fit with experimental data well. Increasing the ambient pressure changes the phase transition mechanism to heat transfer dominated. The phase change mechanisms are depending on ambient conditions and fuel. <br
Keywords: Supercritical; Phase Change; n-Alkanes; Diesel Spray